Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.5 - Integrated Review - Summary on Rational Expressions - Page 526: 3


The solution is 3

Work Step by Step

$\frac{1}{x}$+$\frac{2}{3}$=$\frac{3}{x}$ 3x($\frac{1}{x}$+$\frac{2}{3}$)=3x$\frac{3}{x}$ 3x$\frac{1}{x}$+3x$\frac{2}{3}$=3x$\frac{3}{x}$ 3+2x=9 2x=6 x=3 The solution is 3 Check Let x=3 $\frac{1}{x}$+$\frac{2}{3}$=$\frac{3}{x}$ $\frac{1}{3}$+$\frac{2}{3}$=$\frac{3}{3}$ $\frac{3}{3}$=$\frac{3}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.